Turning waste into wellness: sustainable soap from beef (bos taurus) tallow and butterfly pea flower (clitoria ternatea) - Fadzil, Adibatul Husna; Zulkifli, Norsakina Zurina; Salleh, Nunshaimah; Ali, Rosliza; Mohd Noor, Adibah; Yaacob, Yanti; Mohamad Shukari, Khairol Harmi (2025)
This study investigates the formulation of sustainable soap using Bos taurus tallow (beef tallow), Olea europaea (olive oil), and Clitoria ternatea (butterfly pea flower) extract, with the goal of reusing waste materials while improving soap quality. The objectives were to explore the potential benefits of using animal fat waste in soap production and to enhance product usability by incorporating natural ingredients suitable for sensitive skin. The chemical properties of the soaps were analysed, and their foaming performance, solubility, pH, moisture retention, and skin compatibility were evaluated.